Near-Unity Nitrate to Ammonia conversion via reactant enrichment at the solid-liquid interface - Liao, Wanru; Wang, Jun; Tan, Yao; Zi, Xin; Liu, Changxu; Wang, Qiyou; Zhu, Li; Kao, Cheng-Wei; Chan, Ting-Shan; Li, Hongmei; Zhang, Yali; Liu, Kang; et al. (Nature communications, 2025)
Electroreduction of nitrate (NO 3 ‒ ) to ammonia (NH 3 ) is a promising approach for addressing energy challenges. However, the activity is limited by NO 3 ‒ mass transfer, particularly at reduction potential, where an abundance of electrons on the cathode surface repels NO 3 ‒ from the inner Helmholtz plane (IHP). This constraint becomes pronounced as NO 3 ‒ concentration decreases, impeding practical applications in the conversion of NO 3 ‒ -to-NH 3 . Herein, we propose a generic strategy of catalyst bandstructure engineering for the enrichment of negatively charged ions through solid-liquid (S-L) junction-mediated charge rearrangement within IHP. Specifically, during NO 3 ‒ reduction, the formation of S-L junction induces hole transfer from Ag-doped MoS 2 (Ag-MoS 2 ) to electrode/electrolyte interface, triggering abundant positive charges on the IHP to attract NO 3 ‒ . Thus, Ag-MoS 2 exhibits a ~ 28.6-fold NO 3 ‒ concentration in the IHP than the counterpart without junction, and achieves near-100% NH 3 Faradaic efficiency with an NH 3 yield rate of ~20 mg h ‒1 cm ‒2 under ultralow NO 3 ‒ concentrations. Electroreduction of low-concentration NO 3 − to NH 3 is limited by NO 3 − mass transfer. Here, the authors propose a strategy for NO 3 − enrichment through charge rearrangement within the inner Helmholtz plane, achieving near-unity conversion of NO 3 − to NH 3 .